PEMBINAAN PRESTASI OLAHRAGA SEPAKBOLA PADA SSB BARCA DIKABUPATEN TEMANGGUNG TAHUN 2020 (Indonesian Journal for Physical Education and Sport, 2020)
Focus of the problem in this study is how the implementation of soccer sports development coaching at SSB Barca in Temanggung Regency in 2020. The purpose of this study was to determine the implementation of fostering soccer sports achievement at SSB Barca. This research uses a descriptive qualitative approach. Data collection using the method of observation, interviews, and documentation. The subjects in this study were administrators, coaches, and athletes. The data analysis technique used is data triangulation technique. Data analysis with data reduction, data presentation, and drawing conclusions. The results of the research, it can be concluded that the implementation of soccer sports development in SSB Barca is good enough, it can be seen from the aspects of pemassalan, nurseries, achievements, organizations, training programs, human resources, facilities and infrastructure as well as funding.. There is no need for a dual position by the management. Optimizing sponsorship contributions for improving the welfare of SSB Barca athletes.